Analisis Dampak Ekonomi dan Sosial Pembangunan Infrastruktur di Indonesia - Prita Amalia; Yogi Suprayogi; Yudi Azis; Wawan Hermawan; Eksa Pamungkas; Adi Nurzaman; Anhar Fauzan Priyono (PT Penjaminan Infrastruktur Indonesia (Persero), 2021)
Infrastructure projects are expected to deliver positive economic and social impact to the community. However, the model to analyze the economic and social impact is still limited. Therefore, this study aims to develop an economic and social impact model to be used for study the impact of infrastructure projects. The research focuses on several case studies of infrastructure projects which guaranteed by Indonesia Infrastructure Guarantee Fund (IIGF) both PPP (Public-Private-Partnership) Scheme and non-PPP Scheme on telco, water, tourism Sector. These sectors are believed to represented the major infrastructure development that cover both local, national, and international perspectives. The analytical method used to measure economic impacts from infrastructure development is a quantitative approach by using following attributes: Sectoral Economic Analysis, Potential Economic Analysis, Growth Accounting, Input-Output Table Analysis, and Statistical Forecasting. While, to analyse the social impact of infrastructure development, quantitative and qualitative approaches are used by In-depth Interview through questionnaire filling technique and Social Impact Assessment (SIA) method. In addition, this study also used legal approach method. The results show various economic impacts of project investment development, both in terms of potential and realization. Meanwhile, in terms of social impacts, there are various community responses to the realization of project development.